A methodological case study of lead resource movements during the Warring States Period and Western Han Dynasty: Applying kernel density estimation to four lead-barium glass Bi Artifacts. - Wang, Chen; De Ceuster, Sarah; Eremin, Katherine; Laursen, Sarah; Degryse, Patrick (Journal of Cultural Heritage, 2025)
• KDE improves lead isotope analysis in big data contexts for tracing ancient glass lead sources. • Study uncovers multiple lead sources for Pb-Ba glass using large-scale isotope data from China. • The important role of lead isotope analysis and the KDE method in the authentication of museum artefacts. This methodological case study applies lead isotope analysis and Kernel Density Estimation (KDE) to explore the provenance of four lead-barium silicate glass artifacts from the Harvard Art Museums. Through a detailed methodological framework, this study demonstrates how KDE can be used to analyze lead resource distribution and movements. The lead from one artifact, attributed to the Warring States Period, is traced to southern Chinese regions such as Yunnan, Guizhou, Guangdong, or Guangxi. Two artifacts display distinctive lead isotope signatures potentially linked to materials used in the Shang Dynasty, highlighting unique methodological challenges. Another artifact exhibits anomalous lead isotopic and stylistic features, raising the possibility of it stemming from a different cultural context, possibly with lead sourced from Central China. By employing KDE in combination with lead isotope analysis, this case study not only demonstrates the effectiveness of this combination in archaeological provenance research but also offers insights into the use of lead in ancient Chinese glass production. The results reveal multiple lead sources for the glass-making industry during the Warring States Period and the Western Han Dynasty, and further suggest that certain artifacts contain highly radiogenic lead, likely sourced from South China. These findings underscore the utility of KDE as a powerful tool in both provenance studies and the authentication of museum objects.